Studi Perbandingan Nilai Laba Bersih Antara Metode Pencatatan Penyusutan Yang Dilakukan Perusahaan Dengan UU Perpajakan No.17 Tahun 2000 (Kasus pada PT. Dwi Gunung Putera di Bandar Lampung) - Gatot Hidayat; Daniel Yulian; Riswan RISWAN (Universitas Bandar Lampung (UBL), 2011)
The preparation of financial statements for fiscal purposes, has no provisions that must be complied with in the Tax Act No. 17 of 2000. However, often occur in the preparation of the financial statements prepared by the company's fiscal. The purpose of this study was to determine whether there is a difference between the straight-line method to the declining balance method at the company. The hypothesis is that the cost of depreciation of fixed assets is greater than the company calculated depreciation calculations by Tax Law No.. 17 of 2000, which is caused by differences in the calculation method used and the amount of rates.The analysis used was a qualitative analysis and quantitative analysis. From the research and analysis done can be seen the difference net profit before tax of the company is Rp. 210 438.550 and net profit before tax is a tax of Rp. 216.056.782. Resulting in the difference in the amount of tax of Rp. 1,685,469.66. Or in other words, the state income from taxes on the difference between the methods of recording methods used by the company with the method according to the Tax Law No. 17 of 2000 was reduced by Rp1.685.469, 66. On this mistake, companies subject to administrative sanctions 2% since the tax up to the issuance SKPKB. The administrative penalty calculation is 2% x Rp. = 1,685,469.66. Interest is added to the amount of the tax deficiency owed tersebut.Untuk deal with them, then the company should use the declining balance method used by taxation, so there is no imposition of administrative sanctions by 2% in the financial statements.